Real-World Treatment Patterns and Outcomes of Intraluminal Ablative Therapies in Noninvasive Urethral Carcinoma: A National Cancer Database Analysis. - Luna Velasquez, Eusebio; Mundra, Vatsala; Titus, Renil S.; Xu, Jiaqiong; Riveros, Carlos; Kaushik, Dharam; Singh, Amar; Somawardana, Suran; Wallis, Christopher J. D.; Satkunasivam, Raj (Current Oncology, 2026)
Simple Summary: In this study of patients with early-stage urethral cancer, we found that treatment choices were influenced by tumor location and how aggressive it appeared under the microscope. Patients treated at academic hospitals were more likely to undergo surgery. In men with cancer in the part of the urethra near the prostate, combining ablation with topical treatments was linked to better survival compared to ablation alone. These results suggest that some patients with early-stage urethral cancer may benefit from less invasive, organ-sparing approaches when chosen carefully based on their individual risk. Objective: To evaluate treatment patterns, predictors of treatment selection, and overall survival (OS) in patients with noninvasive (Ta–Tis) urothelial carcinoma of the urethra (UUC). Patients and Methods: We conducted a retrospective cohort study of adults diagnosed with noninvasive UUC (stage Ta or Tis, N0, M0) between 2018 and 2021 using the National Cancer Database. Patients were categorized into prostatic and non-prostatic urethral cohorts. Treatment groups included endoluminal ablation alone, ablation combined with topical intraluminal therapy, urethrectomy, and no subsequent treatment. Multinomial logistic regression was used to identify predictors of treatment selection. The OS was assessed using Kaplan–Meier and multivariable Cox regression, with separate models for each anatomical cohort. Results: A total of 436 patients were included (185 non-prostatic, 251 prostatic); 91.9% (n = 401) were male. Ablation alone was the most common treatment in both cohorts (non-prostatic: 57.3%; prostatic: 62.6%), followed by urethrectomy (non-prostatic: 21.1%) and ablation plus topical therapy (prostatic: 20.3%). In the non-prostatic cohort, high-grade histology (OR 15.15; 95% CI, 3.82–60.04) and Tis stage (OR 3.27; 95% CI, 1.10–9.69) were associated with increased odds of urethrectomy. In the prostatic cohort, high-grade histology was associated with increased use of urethrectomy (OR 59.29; 95% CI, 4.61–763.17) and ablation plus topical therapy (OR 3.09; 95% CI, 1.21–7.90). Tis stage was also associated with ablation plus topical therapy (OR 2.53; 95% CI, 1.14–5.62). This treatment approach was associated with improved OS compared with ablation alone (HR 0.18; 95% CI, 0.05–0.60; p = 0.005). Conclusions: Treatment selection differed substantially by tumor location, stage, and grade, reflecting both treatment selection in noninvasive UUC varied by tumor location, grade, and stage. In prostatic tumors, ablation plus topical therapy was associated with improved survival, supporting its role as a risk-adapted, organ-sparing strategy in selected patients.